OPTIMALISASI LINGKUNGAN KERJA PADA PROSES PERAKITAN PRODUK PADAT KARYA MENGGUNAKAN PENGUJIAN RESPONSE SURFACE METHODOLOGY - Anwar, Fahri; Erniyani, Erniyani; Romadin, Achmad; Cahyani, Vika Puji; Baharuddin, Siti Ruqaiyah (Universitas Putera Batam, 2025)
This research discusses work ergonomics based on influencing factors including noise levels, lighting, and temperature to increase worker productivity to achieve production targets and protect workers from work fatigue on an ongoing basis. Systematic analysis is used with initial experiments to evaluate and then optimize parameters such as lighting, noise, and temperature. These factor dimensions can influence workers' skills and influence work productivity and work fatigue. The response surface method methodology is used to optimize parameters. The findings from the research showed that the optimal level with the scenario was that the most suitable noise level was 55.17 dB, the optimal environmental temperature was 26.35°C, and the optimal lighting level reached 2983 Lux. With this combination of conditions, knitting assembly time can be minimized to 12 seconds per unit. The novelty of this research work lies in its application to labor-intensive industries with skilled workers as production personnel where these factors can influence work productivity. The obtained regression model can be widely used for further research and adjust parameters based on various data such as anthropometry.